Hydrological risk transfer planning under the drought \"severity-duration-frequency\" approach as a climate change impact mitigation strategy - Guzman Arias, Diego Alejandro (2018)
Climate change and increasing water demands prioritize the need to implement planning strategies for urban water security in the long and medium term. However, risk planning requires robust and timely financial support during and after the disaster. Therefore, risk transfer tools, such as insurance, have emerged as an effective strategy to ensure financial resilience and as an element that could encourage the implementation of hydrological risk reduction mechanisms. Among the main insurance design problems are the lack of information on the real drought impacts and climate uncertainty, which may incur adverse selection and/or moral hazards among the most common drawbacks in insurance practice. Currently, most of the income from water utility companies is based on water resources management, therefore during prolonged drought periods these economies can be strongly affected, despite having robust storage schemes as support. Thus, this thesis proposes an insurance plan for the water utility company of the State of Sao Paulo (SABESP) to deal with revenue reductions during long drought periods. The methodology is implemented on the MTRH-SHS model, developed under ex-ante damage cost calculation through the risk-based approach. The synthetic (\'what-if\') approach uses a \"set of change drivers\" to estimate the optimal premium through a multiyear insurance contract (MYI). The methodology integrates the hydrological simulation procedures under radiative climate forcing scenarios RCP 4.5 and 8.5, from the regional climate model outputs Eta-HadGEM and Eta-MIROC5, with time horizons of 2007-2040, 2041-2070, and 2071-2099, linked to the Water Evaluation and Planning system (WEAP) hydrologic model and under stationary and non-stationary water supply demand assumptions. The model framework is applied to the Cantareira Water Supply System for the Sao Paulo Metropolitan Region, Brazil, with severe vulnerability to droughts. As a result, the evaluated indexes showed that multi-year contracts with drought coverage higher than 240 days offer better financial performance than contracts with wider coverages. Moreover, this MYI adopted in the installed storage residual risk generates both a higher level of solvency for the insurance fund in the long term and annual average premiums closer to the expected revenue reductions by scenario. Finally, the approach can help the systematic evaluation of moral hazards and adverse selection. In the first case, the progressive evaluation must generate useful information to change or maintain the behavior of both the insured and insurers considering future risks related to climate change. In the second case, the multi-scenario valuation can help the insurer to set price thresholds, offering risk differential cover options in the premium value.